Status of COVID-19 vaccination in patients undergoing dialysis in China: a national cross-sectional study (2022) - Li, Ping; Zhao, Delong; Wang, Hong; Niu, Yue; Zhou, Jianhui; Liu, Weicen; Cao, Xueying; Ma, Zhifang; Pan, Sai; Liang, Yuan; Sun, Xuefeng; Cai, Guangyan; et al. (Frontiers in Public Health, 2025)
IntroductionDue to their comorbidities and frequent exposure to healthcare settings, patients undergoing dialysis are at a high risk of developing severe COVID - 19. However, there are no customized vaccination guidelines for this group in China. This study had two aims: to systematically evaluate the current status of COVID - 19 vaccination among Chinese dialysis patients and to offer a basis for policy - making and further research.MethodsThis study was conducted across all provinces in mainland China using the stratified randomization method. Electronic questionnaires were distributed to patients undergoing dialysis.ResultsConducted as a national cross - sectional study from May to July 2022, it involved 131,149 dialysis patients from 2,865 centers. The study examined vaccination coverage, the barriers to vaccination, and the safety of vaccines. Only 21.0% received ≥1 vaccine dose, predominantly inactivated vaccines (84.5%). Adverse reactions occurred in 19.0%, with higher rates for adenovirus vector vaccines (27.3%) than for recombinant protein (19.4%) and inactivated vaccines (18.5%, P < 0.001). Among unvaccinated patients, 53.5% faced institutional barriers (e.g., site refusal or lack of recommendations), while 88.7% had no contraindications. Older age (OR = 1.32, 95% CI 1.28–1.36), female gender (OR = 1.18, 1.14–1.22), and hemodialysis (OR = 1.12, 1.06–1.19) predicted non-vaccination.ConclusionIn general, this study highlights critical barriers to COVID-19 vaccination in dialysis patients: guideline gaps, patient hesitation, and non-specific vaccination settings. Recommendations include updating guidelines to prioritize this population, training non-specialized staff, and launching dialysis center-based vaccination programs. Future research should investigate vaccine immunogenicity in dialysis patients to refine booster strategies.